Стимулирование и нормирование труда преподавателей, участвующих в разработке и внедрении технологий дистанционного обучения - Каутс, В. И. (УАДО, 2002)
Professional skill and amount of teachers’ work, participating in distant learning technologies development and introduction into the educational process, are estimated. The problem of norm-setting of time taken to perform this type of activity is set and the methods to solve it are offered. The characteristic of possible approaches to stimulate teachers for participation in the promoting the distant learning into the education process is given.
Keywords: нормирование труда преподавателей; дистанционне обучение